Redes de intera??es entre plantas e borboletas visitantes florais em gradiente altitudinal - Oliveira J?nior, Augusto dos Santos (2013)
The approach to the study of complex networks used for networks of interactions allows the identification of emergent properties such as nestdness, modularity and specialization. Consequently, we hypothesize that mutualistic networks between plants and butterflies visiting flowers in higher altitudes are characterized by few species, with low feeding selectivity. We developed the study using two organizational levels: local and global. The local level comprised mutualistic networks in two hills located in the Chapada Diamantina. The global level comprised mutualistic networks in different regions of the globe. For each network, we evaluated the relationship between altitude, modularity, nestdness and specialization. No network metric shoed a consistent change associated with altitudinal variation, not in the local and global levels. Thus, the structure of interaction networks between butterflies visiting the flowers and plants does not respond to changes in altitude, what we are left understand what factors may be determinants for this interaction.